DISTRIBUTION OF URANIUM IN WATER OF GRESIK COASTAL WATERS - June Mellawati (Universitas Gadjah Mada, 2009)
Determination of uranium in water sample at Gresik coastal waters around Gresik industrial area have been carrid out. The purpose of research is to find the distribution of uranium at the coastal where the phosphate industry standing and potencially to contribute uranium pollutant to the waters. The measurement of uranium was pasive of Gamma Spectrometry, and uranium was measured as 234Th (uranium daughters) on 92.80 and 1001.03 keV gamma energies. Sea water sample was taken up by water pump sampler as a vertical mixing. The sample was sampling on the highest tide and lowest ebb, at the east season (March-August) west season (September-February). The concentration of 238U on higher tide of the west season are range between 0.0016-0.0128 Bq/l, while on lowest ebb of the east season are 0,0013-0,0877 Bq/l. There was significantly different (α= 5%) of uranium concentration in water between two seasons (east and west) in tide and ebb respectively. According to Quality Standard from Dirjen BATAN No.293/Dj/VII/1995 (radioactivity on environment), the concentration of 238U in water obtained from coastal around phosphate industry are still lower than that of recomended values (10.000 Bq/l).